Unity, Division and the Religious Mainstream in Sweden - Willander, Erika 1978- (Cham Springer International Publishing, 2020)
Chapter 1. Introducing the Peculiar Religiosity of Swedes Approach the Religious -- Chapter 2. Religions and Society in Tension -- Chapter 3. When the Mainstream was Lost -- Chapter 4. Mainstream Understandings of the Religious -- Chapter 5. Ways to Find the Mainstream -- Chapter 6. The Religious Mainstream's Affinity with Other's Religion -- Chapter 7. Conclusions in the Light of the Religious Mainstream.
This book presents new conceptual and methodological approaches to studying religiosity in Europe. From her unique background of working with the Church of Sweden statistics and official statistics on the increasing religious diversity in Sweden, Willander illustrates how previous and current methods of analysing religiosity overlook substantial aspects in patterns of affiliation, belief and practice. Unity, Division and the Religious Mainstream in Sweden draws on the sociological imagination in the sociology of religion to offer a new and empirically-driven analytical framework that shifts the focus to religious change in general, and will contribute greatly to ongoing discussions about majority forms of religiosity and their social relevance in contemporary times. It will be of use to students and scholars with a focus on the sociology of religion, as well as sociology, political science, epistemology and media studies.
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Religion and sociology; Emigration and immigration; Social Sciences; Religion And Politics